Drivers of Savings Account Ownership Status: A Cross-Sectional Analysis from Ghana - Yeboah, Augustine Kwadwo (Journal of Social and Development Sciences, 2019)
In view of the evidence that poor savings can inhibit investment decision by borrowers of surplus funds, and that countries with well-established and efficiently utilised financial services have considerably less poverty, the study examines factors influence saving account ownership in Ghana using econometric approach. We used empirical evidence with data sourced from informal market traders in selected major market centres in Ghana. Using probit regression analysis, the results suggest that financial educations, number of income-generating ventures engaged in by the market trader are major predictors of savings account ownership status. Other predictors include demographic characteristics such as gender, age, marital status and number of dependents. It is, therefore, recommended that banks and financial institutions should intensify financial education strategies to boost savings mobilization. Government’s policy intervention should be directed towards informal sector enterprise development to the crowd in revenue in order to motivate decisions to save. Also, the National Board for Small Scale and informal Businesses in Ghana should intensify education on how to sustain diverse income generation ventures to fetch income from multiple sources in order to encourage behavioural intentions to save.